Effect of ageing treatment on fatigue crack growth of die forged Al-5.87Zn-2.07Mg-2.42Cu alloy. (15th June 2019) - Li, Yao; Xu, Guofu; Liu, Shichao; Peng, Xiaoyan; Yin, Zhimin; Wang, Li; Liang, Xiaopeng
Highlights: The effect of precipitates on fatigue crack growth of alloys is discussed. The effect of grain orientation on crack growth of the alloy was studied by EBSD. This paper elaborates on the influencing factors of crack growth by building a model. Abstract: The fatigue-crack growth of the die-forged Al-5.87Zn-2.07Mg-2.42Cu alloy at different ageing conditions: peak aged (T6), over aged (T73) and retrogression and re-ageing (RRA), has been examined in the study. The RRA alloy has the highest resistance to fatigue crack initiation. With increasing stress intensity range (Δk), the T73 sample has the largest expansion rate and it is the smallest for the RRA sample. In the second stage of crack propagation, the crack-growth rate is the largest for the T6 specimen and smallest for the RRA specimen. The crack propagation mode of the alloy in different ageing conditions is mainly based on transgranular expansion. Intergranular expansion was also observed in the T73 state and significant secondary cracks were observed in the RRA sample.